Measuring The Impact of Credit on The Welfare of Rural Farmers in Akwa Ibom State, Nigeria - Nsikak-Abasi Etim; Glory Edet (Newinera Publisher, 2021)
Majority of the poor in Nigeria lack access to basic financial services which are a sine qua non for improved livelihood. In most cases, they are often excluded from formal opportunities for financial services leaving them only with informal alternatives. But credit availability to the poor in the rural areas is critical to reducing poverty. An empirical study was conducted to measure the impact of agricultural credit of the welfare of farmers. Multistage sampling procedure was employed to select the farmers. Questionnaires were employed to collect data. Multiple regression analysis and chow test were for analyses. Results revealed that the mean age and years of education of farmers were 12 and 31 years respectively. Findings also showed that the most critical factors impacting the welfare of farmers were marital status, marriage type, educational level, farm size, off-farm income, labour, type of enterprise, labour and access to modern farming inputs. Policies to encourage human capital development of rural farmers would be a rational decision.